Morphological Research between Rukn Al-Din Al-Istrabadi and Al-Khader Al-Yazdi in their explanations on Al-Shafia - Fadel Al-Harkani, Musa Jaafar (Opción, 2019)
Arab scholars have embarked on rooting linguistic grammar at its four levels: the morphological, grammatical, phonological, and semantic level, and their first books were comprehensive of all of this, as there is no separation between them as we see this clearly in the book Sibawayh and Al-Muqtazib, and others, except that the subsequent stages of time in which the Arabs lived required nature Science is authorship in careful specialization, this is on the one hand, and on the other hand: it was a difficult matter that made many authors make a chapter for him in the end of their books, and these and other circumstances made some scholars need to compose complete books on exchange, such as healing and fair, except that This Its huge texts were marred by a lot of diffi- culty and ambiguity, which made many linguists have to explain these texts, so a new stage of authorship appeared to us, namely annotations. Among the famous texts: Al-Shafiyyah, which is an author in the science of exchange. The explanation was covered by explanation, detailing, commenting, explanation, acceptance and approval. I presented two important explanations in my es- timation, and I presented controversial matters that showed the opinions of the explanation, and showed their agreement and their difference to what Ibn Al-Hajib went to in his shafi after presenting this to the opinions of scholars, and thus he sheds light on opinions that did not get a lot of interest from re- searchers and scholars in studying a budget. Before delving into the presenta- tion of this, it is necessary to define, even briefly, the owner of the hospital and the owners of the explanation who are the subject of the study.